An insight into pharmacokinetics and dose optimization of antimicrobials agents in elderly patients - Fu, Guanshuang; Sun, Weijia; Tan, Zhaoyi; Liang, Beibei; Cai, Yun (Frontiers in Pharmacology, 2024)
The global elderly population is on the rise, and infections tend to have a higher mortality rate among older individuals. Aging is associated with the progressive impairment of multi-organ function, which can impact the pharmacokinetics of antimicrobials, potentially leading to the failure of anti-infective therapy. With the increasing life expectancy, a significant growth in the elderly demographic, and the escalating costs of healthcare, gaining a thorough understanding of pharmacokinetic changes in the elderly holds crucial clinical significance. This review compiles findings from published studies, offering a comprehensive overview of the pharmacokinetics of various antimicrobials in both adults and the elderly. Furthermore, it delves into advancements in pharmacokinetic methods specific to the